Genome comparisons provide insights into the role of secondary metabolites in the pathogenic phase of the Photorhabdus life cycle. (December 2016) - Tobias, Nicholas; Mishra, Bagdevi; Gupta, Deepak; Sharma, Rahul; Thines, Marco; Stinear, Timothy; Bode, Helge
Abstract Background Bacteria within the genusPhotorhabdus maintain mutualistic symbioses with nematodes in complicated lifecycles that also involves insect pathogenic phases. Intriguingly, these bacteria are rich in biosynthetic gene clusters that produce compounds with diverse biological activities. As a basis to better understand the life cycles ofPhotorhabdus we sequenced the genomes of two recently discovered representative species and performed detailed genomic comparisons with five publically available genomes. Results Here we report the genomic details of two new referencePhotorhabdus species. By then conducting genomic comparisons across the genus, we show that there are several highly conserved biosynthetic gene clusters. These clusters produce a range of bioactive small molecules that support the pathogenic phase of the integral relationship thatPhotorhabdus maintain with nematodes. Conclusions Photorhabdus contain several genetic loci that allow them to become specialist insect pathogens by efficiently evading insect immune responses and killing the insect host.